High‐Throughput and Controllable Fabrication of Soft Screen Protectors with Microlens Arrays for Light Enhancement of OLED Displays. Issue 10 (5th August 2020) - Ding, Yekai; Lin, Yinyin; Zhao, Lidan; Xue, Chang; Zhang, Mengying; Hong, Yaying; Peng, Suili; Wen, Weijia; Wu, Jinbo
Abstract: In this work, soft polydimethylsiloxane (PDMS) screen protectors with microlens arrays (MLAs) are fabricated through a feasible high‐throughput approach. Based on the lateral size scaling effect during discontinuous dewetting, desired SU‐8 convex MLAs with simultaneously controlled focal length ( f ) and numerical aperture (NA) are produced on a single substrate. A replication technique is employed to prepare PDMS MLAs with the same structure as that of the SU‐8 MLAs. The contact angle and other optical parameters of the MLAs can be tuned over a wide range based on the number of sliding times and lateral size. When the diameter of the MLAs decreases from 100 to 10 µm, the curvature changes from 0.07 to 0.17 for the single‐layer MLAs and from 0.15 to 0.31 for the three‐layer MLAs. The enhancement effect of MLAs on the light from wide‐angle organic light‐emitting diode (OLED) packaging modules is investigated. It is found that PDMS films containing MLAs can increase the brightness of an OLED by 14.13%. The fabricated PDMS concave MLAs can serve as flexible screen protectors to shield OLEDs from damage while enhancing the brightness to improve the energy efficiency. Abstract : The SU‐8 convex microlens arrays (MLAs) with controlled focal length and numerical aperture on a single substrate is prepared by the sliding method. The soft polydimethylsiloxane (PDMS) with MLAs is fabricated by a replication technique. The PDMS concave MLAs can serve as flexible screen protectors to shield organic light‐emitting diodes (OLEDs) from damage while enhancing the brightness to improve the energy efficiency.